Program Riset Ilmiah Imre Lakatos dan Analisisnya dalam Karya Tulis Mahasiswa IAIN Purwokerto (Studi atas Skripsi Mahasiswa Prodi SAA tahun 2019) - Harisman Harisman (Universitas Darussalam Gontor, 2020)
The study of scientific buildings will never be finished. Scholars are always offering the latest ideas to develop science. One of them is the Scientific Research Program initiated by Imre Lakatos.Departing from Popper's Falsification and Kuhn's Paradigm Shifting, Lakatos developed a new scientific direction; the Research Program. Lakatos' idea rests on three main aspects: a hard core, the protective belt and a series of theories. A sturdy protective belt will strengthen a hard core. Meanwhile, the protective belt is supported by a series of theories.Then, how is the application to real research? Especially for student thesis.This research is based on a literature review of the idea of Imre Lakatos, then apply it to student theses of IAIN Purwokerto (Religions Studies Concentration) and then give commensurate criticism.the conclusion, that the Imre Lakatos Scientific Research Program provides a new discourse on theories that were previously deemed a failure. Its failure is not the essence of the theory, but rather the weak supporting theory. As for the analysis related to the Student thesis, that there are still many deficiencies in the protective belt to establish a hard core of the topic.